Analisa Pelanggaran Kode Etik Akuntan Publik Pada PT Garuda Indonesia Tbk - Sukmadiningrat, Fitriani; Janna, Ijratul; Harahap, Yuliana Ilya; Sari, Murti; Saridawati Saridawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Breaches of the code of ethics may harm the auditor's standing and cast doubt on the audit findings. The purpose of this literature analysis was to analyse instances of breaches of the auditor's code of ethics in the PT Garuda case in Indonesia. Additionally, it aimed to provide a comprehensive summary and critical assessment of the case. According to the study, the auditor who examined PT Garuda has breached many aspects of the auditor's code of ethics, such as honesty, impartiality, professional conduct, and competence. The auditor is also accountable for any inaccuracies found in a company's yearly financial statements. The auditor conducts the audit procedure without identifying any faults or adjustments. Subsequently, the Minister of Finance imposed a 12-month suspension on the auditor's licence.